2013
DOI: 10.1186/1748-717x-8-66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of external radiation in a co-culture model of endothelial cells and adipose-derived stem cells

Abstract: BackgroundThe inflammatory response clinically observed after radiation has been described to correlate with elevated expression of cytokines and adhesion molecules by endothelial cells. Therapeutic compensation for this microvascular compromise could be an important approach in the treatment of irradiated wounds. Clinical reports describe the potential of adipose-derived stem cells to enhance wound healing, but the underlying cellular mechanisms remain largely unclear.MethodsHuman dermal microvascular endothe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 26 publications
2
38
0
6
Order By: Relevance
“…Die zellbiologischen Interaktionen von Fettstammzellen mit den relevanten Zellarten der Wundheilung wurden in der Vergangenheit u. a. von der Arbeitsgruppe der Autoren untersucht [13]. Hier wurde gezeigt, dass die direkte Interaktion von Fettstammzellen mit Endothelzellen und Fibroblasten einen modulierenden Effekt auf die Entzündungsreaktion nach externer Bestrahlung ausübt.…”
Section: Rolle Adipogener Stammzellenunclassified
See 3 more Smart Citations
“…Die zellbiologischen Interaktionen von Fettstammzellen mit den relevanten Zellarten der Wundheilung wurden in der Vergangenheit u. a. von der Arbeitsgruppe der Autoren untersucht [13]. Hier wurde gezeigt, dass die direkte Interaktion von Fettstammzellen mit Endothelzellen und Fibroblasten einen modulierenden Effekt auf die Entzündungsreaktion nach externer Bestrahlung ausübt.…”
Section: Rolle Adipogener Stammzellenunclassified
“…Der Anstieg wundheilungsrelevanter und proinflammatorischer Marker nach externer Bestrahlung von Fibroblasten und Endothelzellen scheint durch die Kokultur mit adipogenen Stammzellen moduliert zu werden. Auch die Marker der endothelialen Dysfunktion ICAM und VCAM konnten in vitro durch adipogene Stammzellen moduliert werden [13]. Die vorliegenden In-vitro-Daten unterstützen die Hypothese, dass adipogene Stammzellen positive Effekte auf bestrahlte Wunden ausüben könnten [13].…”
Section: Rolle Adipogener Stammzellenunclassified
See 2 more Smart Citations
“…Smith et al (28) investigated that dermal fibroblasts down-regulate expression of ICAM1, VCAM1, and MMP11 in response to MSCs and suggested that downregulation of ICAM1 expression by dermal fibroblasts may be necessary for resolution of inflammation during wound repair. Haubner et al (29) found the increased expression of cytokines and adhesion molecules as ICAM-1 by human dermal microvascular endothelial cells after external radiation is mitigated in the co-culture setting with human adipose-derived stem Integrins are the main cell surface receptors for proteins within the extracellular matrix (ECM). They underpin cell adhesion and migration and are also involved in cell proliferation, programmed cell death, and differentiation (30).…”
Section: Results Of Wound Healing According To Mcroscopic Signs Aftermentioning
confidence: 99%